2009
DOI: 10.4049/jimmunol.0900008
|View full text |Cite
|
Sign up to set email alerts
|

Lentivector Immunization Stimulates Potent CD8 T Cell Responses against Melanoma Self-Antigen Tyrosinase-Related Protein 1 and Generates Antitumor Immunity in Mice

Abstract: Recombinant lentivector immunization has been demonstrated to induce potent CD8 T cell responses in vivo. In this study, we investigated whether lentivector delivering a self/tumor Ag, tyrosinase related protein 1 (TRP1), could stimulate effective antitumor T cell responses. We found that immunization with lentivector expressing mutated TRP1 Ag elicited potent CD8 T cell responses against multiple TRP1 epitopes. Importantly, the activated CD8 T cells effectively recognize wild-type TRP1 epitopes. At peak times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 43 publications
2
49
0
Order By: Relevance
“…2,45 About the lentiviral vectors, recent data from Liu et al showed the capacity of a lentivector carrying self/melanoma antigen to promote rupture of the immune tolerance against self/melanoma derived epitopes in mice. 25 In this study, we found that immunization of HHD mice with recombinant lentivirus carrying hTERT induced CTLs against hTERT epitopes and also resulted in high expansion of CD8 T cells specific for self/mouse TERT epitopes (p572 and p988) shared between the 2 species. 31,33 Furthermore, the self/p572-specific CD8 T response generated with lv-hTERT vector was stronger than one elicited with the heteroclitic peptide pY572 plus adjuvant vaccination (pY572/adjuv).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…2,45 About the lentiviral vectors, recent data from Liu et al showed the capacity of a lentivector carrying self/melanoma antigen to promote rupture of the immune tolerance against self/melanoma derived epitopes in mice. 25 In this study, we found that immunization of HHD mice with recombinant lentivirus carrying hTERT induced CTLs against hTERT epitopes and also resulted in high expansion of CD8 T cells specific for self/mouse TERT epitopes (p572 and p988) shared between the 2 species. 31,33 Furthermore, the self/p572-specific CD8 T response generated with lv-hTERT vector was stronger than one elicited with the heteroclitic peptide pY572 plus adjuvant vaccination (pY572/adjuv).…”
Section: Discussionmentioning
confidence: 69%
“…23,24 More recently, Liu et al showed that vaccination with a lentivector carrying mouse melanoma self/ antigen can stimulate strong antiself/melanoma CD8 T-cell responses that induce successful tumor regression, thus supporting the ability of lentivector to break immune tolerance. 25 In this study, taking advantage of the high homology between hTERT and mTERT, 26 we constructed a lentivector expressing the full-length hTERT gene (lv-hTERT) and evaluated its immunogenicity and antitumor effect in an animal model of HLA transgenic mice. We compared the efficacy of the recombinant lv-hTERT vaccination with the hTERT peptide vaccination containing CD8-restricted epitopes.…”
Section: Introductionmentioning
confidence: 99%
“…Lentivectors have major advantages over other recombinant viral vectors, because most hosts lack of pre-existing lentivector-specific immunity, and replication incompetent lentivectors typically elicit only Ag-focused immunity due to expression only of the engineered heterologous gene rather than the expression of endogenous viral genes in the vector (6). In addition, recent studies have shown the elicitation of protective antiviral and anticancer immunity by lentivectors, suggesting that recombinant lentivectors are promising vaccine candidates (9)(10)(11)(12).…”
Section: D8mentioning
confidence: 99%
“…71,72 On account of this immunogenicity, lentiviruses are now being developed as novel genetic vaccines. [73][74][75] Although this study did not deal with the immune response to lentiviral vectors in the CNS, caution is also warranted for CNS delivery.…”
Section: Immunobiology Ofmentioning
confidence: 99%